evaluasi pengelolaan dan pelaporan dana bantuan operasional sekolah (BOS) reguler pada SMP Kristen Koha: The Evaluating The Management And Reporting Of Regular School Operational Assistance (Bos) Funds At Koha Christian Middle School - safryanto manintang; Jessy D. L. Warongan; Djeini Maradesa (Jurnal LPPM Bidang EkoSosBudKum (Ekonomi,Sosial,Budaya, dan Hukum), 2023)
The School Operational Assistance Fund (BOS) is a government assistance program to provide funding for non-personnel costs for education units. The purpose of this study was to evaluate the management and reporting of BOS funds. The research method used is a qualitative approach. Sources of data are taken from primary data and secondary data. The data collection procedure used interview, observation and documentation methods. The results of this study show. (1) The management of BOS funds is in accordance with the technical instructions for managing the 2021 BOS funds, the management of BOS funds is only carried out by the principal and the school treasurer. (2) Reporting on BOS Funds is in accordance with the technical guidelines for managing BOS funds in 2021, where schools make books of BOS funds.